PAUD is My Second Child: How Early Childhood in Indonesia Strives to Develop - Heny Solekhah (International Journal of Emerging Issues in Early Childhood Education, 2019)
This research is aimed to investigate how the teachers of Early Childhood Education (ECE) in Indonesia or Pendidikan Anak Usia Dini (PAUD) have been struggling to sustain and develop their schools. The data was collected through a focus group discussion with teachers in Kelompok Bermain (KB) from four sub-districts in Kendal, Central Java. It is followed by individual interviews and the teachers’ document analysis. The government policies are also gathered and analysed to know to what extent the government supports the teachers and their schools. The research found that despite the different reasons for being PAUD teachers, they established (ECE) from ‘zero’ and put their schools as a priority over themselves; being proactive and communicative the only ways to develop both their professionalism and institutions; Dana Desa and Dana Kelurahan are two desired financial resources; and they hope that the government could raise their status from non-formal educators to be formal and bring equality. In conclusion, the teachers have struggled to advance their professionalism and institutions despite disadvantaged circumstances and expecting that in the future they will gain more government support.DOI: http://doi.org/10.31098/ijeiece.v1i2.50